Palaeoclimatic reconstruction from Loch Lomond Readvance glaciers in the West Drumochter Hills, Scotland - Benn, DI; Ballantyne, Colin Kerr (Journal of Quaternary Science, 2005)
Geomorphological mapping in the West Drumochter Hills provides evidence of a readvance of locally nourished glaciers during the Loch Lomond (Younger Dryas) Stade, in the form of an icefield 67.7 km(2) in area drained by outlet glaciers. The icefield limits accord broadly with those proposed by Sissons (1980) but all geomorphic, stratigraphic and sedimentological evidence conflicts with a recent proposal that the landforms in the area reflect southwestwards retreat of the last ice sheet. Up-valley continuity of recessional moraines indicates that the ice remained active and close to climatic equilibrium during the earlier stages of glacier retreat, consistent with slow warming following the coldest part of the stade. The pattern of equilibrium line altitudes (ELAs) across the icefield is consistent with transfer of snow by westerly and southerly winds. The ELA of the reconstructed icefield as a whole is 622-629 m, although this figure is likely to be lower than the regional (climatic) ELA because the icefield probably received additional snow blown from adjacent plateau surfaces and slopes. Inclusion of potential snow-blow areas in the ELA calculation yields a value of 648-656 m; the climatic ELA is therefore likely to have lain between 622 and 656 m. Mean June to August temperature at the ELA, based on chironomid assemblages at two sites, falls within the range 4.0 +/- 0.7 degrees C. Empirical relationships between temperature and precipitation at modern glacier ELAs indicate that mean annual precipitation (MAP) at the ELA was 1977 +/- 464 mm, statistically indistinguishable from modern values. Comparison with precipitation values calculated for the Isle of Mull on the west coast suggest that the precipitation gradient across the Central Highlands of Scotland was steeper during the Loch Lomond Stade than at present, probably as the result of efficient scavenging of precipitation from westerly airflows by the West Highland Icefield. Copyright (c) 2005 John Wiley & Sons, Ltd.